Impact of Iceberg Calving on the Retreat of Thwaites Glacier, West Antarctica Over the Next Century With Different Calving Laws and Ocean Thermal Forcing. Issue 24 (18th December 2019) - Yu, Hongju; Rignot, Eric; Seroussi, Helene; Morlighem, Mathieu; Choi, Youngmin
Abstract: Thwaites Glacier, West Antarctica, has been a major contributor to global sea level rise over the past decades. Prior studies illustrated the critical role of ice shelf melt and iceberg calving based on cliff height in driving the retreat of Thwaites glacier. Here, we simulate its evolution with various calving laws and rates of frontal melt by the ocean in the absence of a buttressing ice shelf. Over the next century, we find that volume losses increase by 15–160% with a von Mises calving law compared to the case where the initial ice shelf is kept and the ice front is fixed at its current position, 10–20% with a buoyancy‐driven calving law, and 5–50% with frontal melt caused by ocean thermal forcing. Bed topography exerts the ultimate control on the evolution of Thwaites. In all simulations, once Thwaites Glacier retreats past the western subglacial ridge, the retreat becomes rapidly unstoppable. Key Points: Calving of grounded ice and frontal melt enhance the retreat of Thwaites Glacier compared to a retreat driven by ice shelf melt only The retreat rate increases by 15% to 160% with von Mises calving, 10% to 20% with buoyancy‐driven calving, and 5% to 50% with frontal melt Thwaites Glacier can collapse within a century if ocean forcing and calving retreat its grounding line past the western subglacial ridge